Complete genome analysis of Lactobacillus fermentum SK152 from kimchi reveals genes associated with its antimicrobial activity. Issue 18 (26th August 2017) - Yoo, DongAhn; Bagon, Bernadette B.; Valeriano, Valerie Diane V.; Oh, Ju Kyoung; Kim, Heebal; Cho, Seoae; Kang, Dae-Kyung
Abstract: Research findings on probiotics highlight their importance in repressing harmful bacteria, leading to more extensive research on their potential applications. We analysed the genome of Lactobacillus fermentum SK152, which was isolated from the Korean traditional fermented vegetable dish kimchi, to determine the genetic makeup and genetic factors responsible for the antimicrobial activity of L. fermentum SK152 and performed a comparative genome analysis with other L. fermentum strains. The genome of L. fermentum SK152 was found to comprise a complete circular chromosome of 2092 273 bp, with an estimated GC content of 51.9% and 2184 open reading frames. It consisted of 2038 protein-coding genes and 73 RNA-coding genes. Moreover, a gene encoding a putative endolysin was found. A comparative genome analysis with other L. fermentum strains showed that SK152 is closely related to L. fermentum 3872 and F-6. An evolutionary analysis identified five positively selected genes that encode proteins associated with transport, survival and stress resistance. These positively selected genes may be essential for L. fermentum to colonise and survive in the stringent environment of the human gut and exert its beneficial effects. Our findings highlight the potential benefits of SK152. Abstract : Lactobacillus fermentum SK152 isolated from Korean fermented vegetable, Kimchi, was found to possess antimicrobial activity.